2013
DOI: 10.7224/1537-2073.2012-037
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Exercise in People with Multiple Sclerosis

Abstract: The aims of this study were to explore the feasibility of structured aerobic exercise followed by a period of unstructured physical activity and determine the impact of such exercise on cognition, mood, and quality of life in people with multiple sclerosis (MS). A convenience sample of 9 individuals with relapsing-remitting MS performed 30 minutes of aerobic exercise (upper-and lower-extremity ergometry and treadmill ambulation) twice weekly for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…Attrition rates of PwMS were less than previously observed rates in exercise trials for PwMS which ranged from 18% to 42% (Swank et al, 2013), and also less than the 20% proposed as a measure of trial quality (Schulz andGrimes, 2002, Fewtrell et al, 2008). Moreover, given the level of disability and complexity of everyday life for this population, this rate is not unexpected in a community setting.…”
Section: Discussionmentioning
confidence: 77%
“…Attrition rates of PwMS were less than previously observed rates in exercise trials for PwMS which ranged from 18% to 42% (Swank et al, 2013), and also less than the 20% proposed as a measure of trial quality (Schulz andGrimes, 2002, Fewtrell et al, 2008). Moreover, given the level of disability and complexity of everyday life for this population, this rate is not unexpected in a community setting.…”
Section: Discussionmentioning
confidence: 77%
“…EStim and muscle stretches were not related to any mood changes. In a similar study by Swank and colleagues [75], the BDI Total and Cognitive scores did not change after their 8-week aerobic exercise intervention, but BDI "Somato-Affective" scores improved significantly, with benefits lasting 3 months. In the present study, exercise was not related to BDI Total scores, and the opposite of what Swank et al reported was found for the subscales (exercise dosage was associated with the BDI Cognitive but not Somatic-Affective scores).…”
Section: Exercise and Moodmentioning
confidence: 80%
“…Further, this study included EStim and the comparison study did not, so we cannot compare the EStim outcomes. Swank et al [75] did not find improvements in working memory or verbal learning cognitive domains after an 8-week aerobic exercise intervention, but as they indicated, the short duration of their intervention (8 weeks) may not be sufficient for cognitive changes. The present study's authors agree with this, because most of the cognitive improvements observed with increased exercise dosage were not significant until 3 to 12 months after the start of the current intervention.…”
Section: Exercise and Cognitive Functionmentioning
confidence: 95%
“…In another study, Swank et al (2013) showed that structural cardiorespiratory training can cause improvement in quality of life and emotion of multiple sclerosis patients [ 2 ].…”
Section: Part Imentioning
confidence: 99%